2016
DOI: 10.1515/npf-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Charitable Solicitations Regulation and the Principles of Regulatory Disclosure

Abstract: Today, many regulators' operations publish information derived from registration and reporting by charitable organizations and commercial fundraising firms. Similar publication is found in a variety of situationsrestaurant sanitation notices and hospital re-infection rates, among many others. Recent scholarship has explored the theory of regulatory disclosure, identifying how required disclosures can influence organizational behavior and potentially improve public welfare. An important feature of this theory i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…As shown in Table 1, scholarship on government regulation of charitable solicitation can be grouped into three categories based on regulatory objective: 1) to empower donors to make more informed decisions with their donations, 2) to ensure that donated funds reach the intended beneficiary, and/or 3) to advance an interest of government or a government official rather than the charitable sector (Barber & Farwell, 2016a;Breen, 2009;Irvin, 2005).…”
Section: Rationales For Regulating Charitable Solicitationmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, scholarship on government regulation of charitable solicitation can be grouped into three categories based on regulatory objective: 1) to empower donors to make more informed decisions with their donations, 2) to ensure that donated funds reach the intended beneficiary, and/or 3) to advance an interest of government or a government official rather than the charitable sector (Barber & Farwell, 2016a;Breen, 2009;Irvin, 2005).…”
Section: Rationales For Regulating Charitable Solicitationmentioning
confidence: 99%
“…• Difficult to enforce • Raises constitutional issues regarding free speech Koutoujian, 2012 Benefitting Government • Assumes that the target of enforcement will be unfairly/undeservedly selected over more culpable targets Brody, 2004;Irvin, 2005 lead to changes in donor behavior (Barber & Farwell, 2016a;Brown, Meer, & Williams, 2017;Cnaan, Jones, Dickin, & Salomon, 2011;Irvin, 2005;Portillo & Stinn, 2018;Sloan, 2009;Yörük 2016). Following a review of empirical literature, one author concluded, "It strains credulity that a preponderance of donors would do the necessary research on a charity's cost structure before writing a check…Most persons probably trust their instincts because they know the organization or have heard about its work" (Bowman, 2006, p. 294).…”
Section: False or Faithless Agentmentioning
confidence: 99%
“…Reviews of the history of regulations regarding charitable solicitations (e. g., Barber and Farwell 2016) discuss the steady increase in the number of states that regulate these activities since the early twentieth century. One significant motivation has been to instill confidence in donors, and the general public, that charitable contributions will fund donor-directed activities.…”
Section: Theoretical Motivation and Literature Reviewmentioning
confidence: 99%
“…In recent decades, many states have changed their statutes to emphasize the importance of public disclosure of solicitation-related activities, rather than the need to report these requirements to regulatory staff (Barber and Farwell 2016). Although some have speculated that reporting requirements may induce organizations to change their behavior in response to a perceived increase in awareness by donors, most agree that regulators need to play an active role in enforcing regulations (ibid.).…”
Section: Theoretical Motivation and Literature Reviewmentioning
confidence: 99%
“…The first two of our experiments look to changes in U.S. law. From the late 1970s, U.S. states increasingly enacted laws requiring that any direct-to-donor charitable solicitation include a statement disclosing the fundseeker’s cost-of-fundraising ratio (COFR; Barber & Farwell, 2016). We call these “must disclose” (MD) provisions.…”
Section: Introductionmentioning
confidence: 99%